Propagation mechanisms of guided streamers in plasma jets: the influence of electronegativity of the surrounding gas. (5th June 2015) - Schmidt-Bleker, Ansgar; Norberg, Seth A; Winter, Jörn; Johnsen, Eric; Reuter, S; Weltmann, K D; Kushner, Mark J
Abstract: Atmospheric pressure plasma jets for biomedical applications are often sustained in He with small amounts of, for example, O2 impurities and typically propagate into ambient air. The resulting poorly controlled generation of reactive species has motivated the use of gas shields to control the interaction of the plasma plume with the ambient gas. The use of different gases in the shield yields different behavior in the plasma plume. In this paper, we discuss results from experimental and computational investigations of He plasma jets having attaching and non-attaching gas shields. We found that negative ion formation in the He-air mixing region significantly affects the ionization wave dynamics and promotes the propagation of negative guided streamers through an electrostatic focusing mechanism. Results from standard and phase resolved optical emission spectroscopy ratios of emission from states of N2 and He imply different electric fields in the plasma plume depending on the composition of the shielding gas. These effects are attributed to the conductivity in the transition region between the plasma plume and the shield gas, and the immobile charge represented by negative ions. The lower conductivity in the attaching mixtures enables more extended penetration of the electric field whereas the negative ions aid in focusing the electrons towards the axis.